2010
DOI: 10.1302/0301-620x.92b11.25342
|View full text |Cite
|
Sign up to set email alerts
|

The histology around the cemented Müller straight stem

Abstract: The aim of this study was to obtain detailed long-term data on the cement-bone interface in patients with cemented stems, implanted using the constrained fixation technique. A total of eight stems were removed together with adjacent bone during post-mortem examinations of patients with well-functioning prostheses. Specimens were cut at four defined levels, contact radiographs were obtained for each level, and slices were prepared for histological analysis. Clinical data, clinical radiographs, contact radiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Implants were cemented line-to-line with the final broach (El Masri et al 2010), but in contrast to other canal-filling implants like the Kerboul stem, the medullary canal was prepared with broaches that did not remove cancellous bone in the sagittal plane (Kerboul 1987, Clauss et al 2010). All stems were cemented using a second-generation cementing technique (distal plug, cement syringe, no vacuum-mixing, no jet lavage, and no proximal sealing) with Sulfix-6 bone cement without antibiotics (low viscosity, Zimmer).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Implants were cemented line-to-line with the final broach (El Masri et al 2010), but in contrast to other canal-filling implants like the Kerboul stem, the medullary canal was prepared with broaches that did not remove cancellous bone in the sagittal plane (Kerboul 1987, Clauss et al 2010). All stems were cemented using a second-generation cementing technique (distal plug, cement syringe, no vacuum-mixing, no jet lavage, and no proximal sealing) with Sulfix-6 bone cement without antibiotics (low viscosity, Zimmer).…”
Section: Methodsmentioning
confidence: 99%
“…All of them have shown reliable long-term survival (Fowler et al 1988, Howie et al 1998, Herberts and Malchau 2000, Morscher et al 2005, Buckwalter et al 2006, Hamadouche et al 2008, Clauss et al 2009). The Müller straight stem (MSS; Zimmer, Winterthur, Switzerland) was designed according to the shape-closed concept in order to achieve a press-fit fixation in the anterior-posterior plane with a self-centering effect (Clauss et al 2010). The original MSS was made out of forged CoNiCrMo (Co).…”
mentioning
confidence: 99%
“…The Müller CDH stem was developed for hips with altered anatomy showing small femora, or dysplastic hips presenting an increased CCD angle with a small head, allowing for a wedge-type stem with additional cement fixation. It follows the same cementing philosophy as the original Müller straight stem, however, with extended possible indications [ 18 , 31 ]. For cemented Müller straight stems, Clauss et al [ 13 ] have shown osteolysis to occur mainly in the Gruen zones 6 and 7 with debonding first appearing superolaterally, which is in accordance to the radiological findings of the Müller CDH straight stem.…”
Section: Discussionmentioning
confidence: 99%
“…Subsidence was defined as being an increase of radiolucency between the shoulder of the prosthesis and proximal cement in Gruen zone 1 [ 12 ]. Cortical atrophy of the femur was defined as being a longitudinal thinning of the femoral cortex due to intracortical porosis, without any measurable changes of the diameter of the femur [ 18 ]. Debonding, osteolysis, and cortical atrophy of the femur were evaluated in the Gruen zones [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, the amount of quantitative mechanical data of postmortem cement-bone interface specimens is, in contrast to lab-prepared data, also limited (Miller et al, 2011; Mann et al, 2010; Miller et al, 2010). In the past, studies to post-mortem cement-bone interfaces mainly focused on the histology rather than the mechanical behavior of the interface (Clauss et al, 2010; Bishop et al, 2009; Schmalzried et al, 1993; Jasty et al, 1991). Finally, the FEA models used in this study do not directly match the geometry of the postmortem specimens as a result of the mirroring.…”
Section: Discussionmentioning
confidence: 99%